Cross-linked torlon/P84 hollow fiber membranes for highly selective NH3 separation with enhanced stability - Chang-In Kong; Myeong-Hun Hyeon; Hyeon-Jin Cho; Chae-Young Park; Taehoon Kim; Jong Geun Seong; Cheol Park; Jae-Hyeok Lee; Chang-Ha Lee; Su-Young Moon (Chemical Engineering Journal, 2026)

Facile and rapid fabrication of wearable biosensors via femtosecond laser-directed micro-patterning with large-sized reduced graphene oxide for physiological monitoring - Hae-In Moon; Sungil Kim; Jeong Eun Byun; Young Won Kim; Yeon Wook Jung; Seung Geun Jo; Yujin Shin; Yeoul Kang; Sang Jun Kim; Eun-Su Lee; Hyung-Jong Lee; Min-Cheol Oh; et al. (Chemical Engineering Journal, 2024)

In situ electrolyte replenishment with atmospheric pressure-chemical/electrochemical vapour deposition for molten carbonate fuel cells - Kab In Kim; Jae Kwan Bae; Emilio Audasso; Albert Won Cho; Young Bae Jun; Hyun Seo Park; Seong-Cheol Jang; Yong Soo Cho; Han Sung Kim; Sun-Hee Choi; Sung Pil Yoon (Chemical Engineering Journal, 2023)

Development of high-performance organic photodetectors by understanding origin of dark current density with synthesis of photoconductive polymers - WonJo Jeong; Jinhyeon Kang; Dongchan Lee; Cheol Shin; Hyungju Ahn; Chan So; Jong Ho Won; Dae Sung Chung; Shinuk Cho; In Hwan Jung (Chemical Engineering Journal, 2023)

A Comparative Study of an Anti-Thrombotic Small-Diameter Vascular Graft with Commercially Available e-PTFE Graft in a Porcine Carotid Model - Kyo Seon Lee; Mukhammad Kayumov; Gladys A. Emechebe; Do-Wan Kim; Hwa-Jin Cho; Yun-Jin Jeong; Dong-Weon Lee; Jun-Kyu Park; Chan-Hee Park; Cheol-Sang Kim; Francis O. Obiweluozor; In-Seok Jeong (Tissue Engineering and Regenerative Medicine, 2022)
Background: We have designed a reinforced drug-loaded vascular graft composed of polycaprolactone (PCL) and polydioxanone (PDO) via a combination of electrospinning/3D printing approaches. To evaluate its potential for clinical application, we compared the in vivo blood compatibility and performance of PCL/PDO + 10%DY grafts doped with an antithrombotic drug (dipyridamole) with a commercial expanded polytetrafluoroethylene ( e -PTFE) graft in a porcine model. Methods: A total of 10 pigs (weight: 25–35 kg) were used in this study. We made a new 5-mm graft with PCL/PDO composite nanofiber via the electrospinning technique. We simultaneously implanted a commercially available e -PTFE graft ( n = 5) and our PCL/PDO + 10%DY graft ( n = 5) into the carotid arteries of the pigs. No anticoagulant/antiplatelet agent was administered during the follow-up period, and ultrasonography was performed weekly to confirm the patency of the two grafts in vivo . Four weeks later, we explanted and compared the performance of the two grafts by histological analysis and scanning electron microscopy (SEM). Results: No complications, such as sweating on the graft or significant bleeding from the needle hole site, were seen in the PCL/PDO + 10%DY graft immediately after implantation. Serial ultrasonographic examination and immunohistochemical analysis demonstrated that PCL/PDO + 10%DY grafts showed normal physiological blood flow and minimal lumen reduction, and pulsed synchronously with the native artery at 4 weeks after implantation. However, all e -PTFE grafts occluded within the study period. The luminal surface of the PCL/PDO + 10%DY graft in the transitional zone was fully covered with endothelial cells as observed by SEM. Conclusion: The PCL/PDO + 10%DY graft was well tolerated, and no adverse tissue reaction was observed in porcine carotid models during the short-term follow-up. Colonization of the graft by host endothelial and smooth muscle cells coupled with substantial extracellular matrix production marked the regenerative capability. Thus, this material may be an ideal substitute for vascular reconstruction and bypass surgeries. Long-term observations will be necessary to determine the anti-thrombotic and remodeling potential of this device.

Increased Cysteine Accumulation is Essential for Salt Stress Tolerance in Arabidopsis Halotolerance 2-Like (AHL)-Overexpressing Transgenic Plants - Tinh Van Nguyen; Jeong-In Kim; Cho-Rong Park; Moon-Soo Chung; Cheol Soo Kim (Journal of Plant Biology, 2021)

Poor outcomes of early recurrent post-transplant bloodstream infection in living-donor liver transplant recipients - Si-Ho Kim; Seok Jun Mun; Jae-Hoon Ko; Kyungmin Huh; Sun Young Cho; Cheol-In Kang; Doo Ryeon Chung; Gyu-Seong Choi; Jong Man Kim; Jae-Won Joh; Kyong Ran Peck (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Health risk assessment for multimedia exposure of formaldehyde emitted by chemical accident - Si-Hyun Park; Hui-Been Lim; Hyong-Jin Hong; Hee-Seok Kim; Dan-Ki Yoon; Hye-Won Lee; Hye-Kwan Kong; Jeong-In Jeon; Ji-Won Choi; Eun-Min Cho; Yong-Sung Cho; Cheol-Min Lee (Environmental Science and Pollution Research, 2021)

Considerations in the Development of Small-Diameter Vascular Graft as an Alternative for Bypass and Reconstructive Surgeries: A Review - Francis O. Obiweluozor; Gladys A. Emechebe; Do-Wan Kim; Hwa-Jin Cho; Chan Hee Park; Cheol Sang Kim; In Seok Jeong (Cardiovascular Engineering and Technology, 2020)

Risk factors for development and mortality of invasive pulmonary Aspergillosis in kidney transplantation recipients - Hyeri Seok; Kyungmin Huh; Sun Young Cho; Cheol-In Kang; Doo Ryeon Chung; Woo Seong Huh; Jae Berm Park; Kyong Ran Peck (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Emergence of vancomycin-resistant Enterococcus faecium ST1421 lacking the pstS gene in Korea - Hye Mee Kim; Doo Ryeon Chung; Sun Young Cho; Kyungmin Huh; Cheol-In Kang; Kyong Ran Peck (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Clinical factors influencing the performance of bacterial multiplex polymerase chain reaction in patients with community-onset pneumonia - Ga Eun Park; Kyong Ran Peck; Jae-Hoon Ko; Cheol-In Kang; Sun Young Cho; Doo Ryeon Chung; Nam Yong Lee (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Rice CaM-binding transcription factor (OsCBT) mediates defense signaling via transcriptional reprogramming - Jung-Sung Chung; Sung Cheol Koo; Byung Jun Jin; Dongwon Baek; Seon-In Yeom; Hyun Jin Chun; Man Soo Choi; Hyun Min Cho; Su Hyeon Lee; Wook-Hun Jung; Cheol Woo Choi; Anil Kumar Nalini Chandran; et al. (Plant Biotechnology Reports, 2020)

An inverse agonist of estrogen-related receptor γ regulates 2-arachidonoylglycerol synthesis by modulating diacylglycerol lipase expression in alcohol-intoxicated mice - Yoon Seok Jung; Yong-Hoon Kim; Kamalakannan Radhakrishnan; Jina kim; Don-Kyu Kim; Ji-Hyeok Lee; Hyunhee Oh; In-Kyu Lee; Wook Kim; Sung Jin Cho; Cheol Soo Choi; Steven Dooley; et al. (Archives of Toxicology, 2020)

Clinical effectiveness of oral antimicrobial therapy for acute pyelonephritis caused by extended-spectrum β-lactamase-producing Enterobacteriales - Si-Ho Kim; Kyoung Ree Lim; Hyunju Lee; Kyungmin Huh; Sun Young Cho; Cheol-In Kang; Doo Ryeon Chung; Kyong Ran Peck (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Evaluating the optimal dose of teicoplanin with therapeutic drug monitoring: not too high for adverse event, not too low for treatment efficacy - Si-Ho Kim; Cheol-In Kang; Kyungmin Huh; Sun Young Cho; Doo Ryeon Chung; Soo-Youn Lee; Yae-Jean Kim; Kyong Ran Peck (European Journal of Clinical Microbiology & Infectious Diseases, 2019)

Inappropriate empirical antibiotic therapy does not adversely affect the clinical outcomes of patients with acute pyelonephritis caused by extended-spectrum β-lactamase-producing Enterobacteriales - Si-Ho Kim; Suhyun Oh; Kyungmin Huh; Sun Young Cho; Cheol-In Kang; Doo Ryeon Chung; Kyong Ran Peck (European Journal of Clinical Microbiology & Infectious Diseases, 2019)

Follow-up blood cultures add little value in the management of bacteremic urinary tract infections - HyeJin Shi; Cheol-In Kang; Sun Young Cho; Kyungmin Huh; Doo Ryeon Chung; Kyong Ran Peck (European Journal of Clinical Microbiology & Infectious Diseases, 2019)

Differential regional infarction, neuronal loss and gliosis in the gerbil cerebral hemisphere following 30 min of unilateral common carotid artery occlusion - Ji Hyeon Ahn; Minah Song; Hyunjung Kim; Tae-Kyeong Lee; Cheol Woo Park; Young Eun Park; Jae-Chul Lee; Jun Hwi Cho; Young-Myeong Kim; In Koo Hwang; Moo-Ho Won; Joon Ha Park (Metabolic Brain Disease, 2019)

Pathogenic significance of hemorrhagic pneumonia in hematologic malignancy patients with Stenotrophomonas maltophilia bacteremia: clinical and microbiological analysis - Si-Ho Kim; Min Kyeong Cha; Cheol-In Kang; Jae-Hoon Ko; Kyungmin Huh; Sun Young Cho; Doo Ryeon Chung; Kyong Ran Peck (European Journal of Clinical Microbiology & Infectious Diseases, 2019)

Brain ischemic preconditioning protects against moderate, not severe, transient global cerebral ischemic injury - Jae-Chul Lee; Bich-Na Shin; Jeong Hwi Cho; Tae-Kyeong Lee; In Hye Kim; YooHun Noh; Sung-Su Kim; Hyang-Ah Lee; Young-Myeong Kim; Hyeyoung Kim; Jun Hwi Cho; Joon Ha Park; et al. (Metabolic Brain Disease, 2018)

Factors affecting the public awareness and behavior on antibiotic use - Kyungmin Huh; Doo Ryeon Chung; So Hyun Kim; Sun Young Cho; Young Eun Ha; Cheol-In Kang; Kyong Ran Peck; Jae-Hoon Song (European Journal of Clinical Microbiology & Infectious Diseases, 2018)

Whole-transcriptome analysis of mouse adipose tissue in response to short-term caloric restriction - Seung-Soo Kim; Kyung-Mi Choi; Soyoung Kim; Taesun Park; In-Cheol Cho; Jae-Won Lee; Cheol-Koo Lee (Molecular Genetics and Genomics, 2016)

Is there a relationship between PPARD T294C/PPARGC1A Gly482Ser variations and physical endurance performance in the Korean population? - Han-Jun Jin; In-Wook Hwang; Ki-Cheol Kim; Hyun-Ik Cho; Tae-Hwan Park; Yun-A Shin; Ho-Seong Lee; Ji-Hyun Hwang; Ah-Ram Kim; Kwang-Hee Lee; Ye-Eun Shin; Ji-Yeon Lee; et al. (Genes & Genomics, 2016)

Inhibition effect of phenyl compounds from the Oryza sativa roots on melanin production in murine B16-F10 melanoma cells - Jin-Gyeong Cho; Jeongran Huh; Rak-Hun Jeong; Byeong-Ju Cha; Sabina Shrestha; Dong-Geol Lee; Hee-Cheol Kang; Ji-Young Kim; Nam-In Baek (Natural Product Research, 2015)

Genome-wide association analysis to identify SNP markers affecting teat numbers in an F2 intercross population between Landrace and Korean native pigs - Jae-Bong Lee; Eun-Ji Jung; Hee-Bok Park; Shil Jin; Dong-Won Seo; Moon-Suck Ko; In-Cheol Cho; Jun-Heon Lee; Hyun-Tae Lim (Molecular Biology Reports, 2014)

Comparative transcriptomic analysis to identify differentially expressed genes in fat tissue of adult Berkshire and Jeju Native Pig using RNA-seq - Simrinder Singh Sodhi; Won Cheoul Park; Mrinmoy Ghosh; Jin Nam Kim; Neelesh Sharma; Kwang Yun Shin; In Cheol Cho; Youn Chul Ryu; Sung Jong Oh; Sung Hoon Kim; Ki-Duk Song; Sang Pyo Hong; et al. (Molecular Biology Reports, 2014)

Triterpenoids from Fragaria ananassa calyx and their inhibitory effects on melanogenesis in B16-F10 mouse melanoma cells - Na-Young Song; Jin-Gyeong Cho; Dongmoon Im; Dae-Young Lee; Qian Wu; Woo-Duck Seo; Hee Cheol Kang; Youn-Hyung Lee; Nam-In Baek (Natural Product Research, 2013)

Identification of molecular mechanism controlling P34 gene expression in soybean - Sung Cheol Koo; Jun Su Seo; Min Jung Park; Hyun Min Cho; Mi Suk Park; Cheol Woo Choi; Wook-Hun Jung; Kyoung Hee Lee; Byung Jun Jin; Seok Hyeon Kim; Sang In Shim; Jung-Sung Chung; et al. (Plant Biotechnology Reports, 2013)

Association of the gene encoding stearoyl-CoA desaturase (SCD) with fatty acid composition in an intercross population between Landrace and Korean native pigs - Dyah Maharani; Hee-Bok Park; Jae-Bong Lee; Chae-Kyoung Yoo; Hyun-Tae Lim; Sang-Hyun Han; Sung-Soo Lee; Moon-Suck Ko; In-Cheol Cho; Jun-Heon Lee (Molecular Biology Reports, 2013)

A missense mutation (c.1963A<G) of the complementary component 2 (C2) gene is associated with serum Ca++ concentrations in pigs - Jae-Bong Lee; Chae-Kyoung Yoo; Eun-Ji Jung; Jung-Hye Hwang; Bo-Young Seo; Byeong-Woo Kim; Hyun-Tae Lim; Jung-Gyu Lee; In-Cheol Cho; Hee-Bok Park (Molecular Biology Reports, 2012)

A novel gibberellin 2-oxidase gene CaGA2ox1 in pepper is specifically induced by incompatible plant pathogens - Yeon Lee; Young-Cheol Kim; Soo Yong Kim; In-Jung Lee; Doil Choi; Kyung-Hee Paek; Hye Sun Cho; Suk Yoon Kweon; Jeong Mee Park (Plant Biotechnology Reports, 2012)

QTL analysis of back fat thickness and carcass pH in an F2 intercross between Landrace and Korean native pigs - Chae-Kyoung Yoo; Hyun-Tae Lim; Sang-Hyun Han; Sung-Soo Lee; Moon-Suck Ko; Taeyoung Kang; Jun Heon Lee; Hee-Bok Park; In-Cheol Cho (Molecular Biology Reports, 2012)

Porcine SPP1 gene polymorphism association with phenotypic traits in the Landrace × Jeju (Korea) black pig F2 population - Sang-Hyun Han; Kwang-Yun Shin; Sung-Soo Lee; Moon-Suck Ko; Hong-Shik Oh; In-Cheol Cho (Molecular Biology Reports, 2012)

A promoter polymorphism of MSTN g.−371T>A and its associations with carcass traits in Korean cattle - Sang-Hyun Han; In-Cheol Cho; Moon-Suck Ko; Eun-Young Kim; Se-Pill Park; Sung-Soo Lee; Hong-Shik Oh (Molecular Biology Reports, 2012)

Anti-angiogenic effects of the water extract of HangAmDan (WEHAD), a Korean traditional medicine - Ji-Young Bang; Kyung-Soon Kim; Eung-Yoon Kim; Hwa-Seung Yoo; Yeon-Weol Lee; Chong-Kwan Cho; YoungJin Choi; Hyun-Ja Jeong; In-Cheol Kang (Science China Life Sciences, 2011)

SINE indel polymorphism of AGL gene and association with growth and carcass traits in Landrace × Jeju black pig F2 population - Sang-Hyun Han; Kwang-Yun Shin; Sung-Soo Lee; Moon-Suck Ko; Dong Kee Jeong; Hong-Shik Oh; Byoung-Chul Yang; In-Cheol Cho (Molecular Biology Reports, 2010)

A novel mutation in Hr causes abnormal hair follicle morphogenesis in hairpoor mouse, an animal model for Marie Unna Hereditary Hypotrichosis - In Cheol Baek; Jeong Ki Kim; Kyu-Hyuk Cho; Dal-Sun Cha; Jae-Woo Cho; Jong Keun Park; Chang-Woo Song; Sungjoo Kim Yoon (Mammalian Genome, 2009)

AGHR polymorphism and its associations with carcass traits in Harrwoo cattle - Sang-Hyun Han; In-Cheol Cho; Jin-Hyoung Kim; Moon-Suck Ko; Ha-Yeon Jeong; Hong-Shik Oh; Sung-Soo Lee (Genes & Genomics, 2009)

A rice dehydration-inducible SNF1-related protein kinase 2 phosphorylates an abscisic acid responsive element-binding factor and associates with ABA signaling - Min-Ju Chae; Jung-Sook Lee; Myung-Hee Nam; Kun Cho; Ji-Yeon Hong; Sang-A Yi; Seok-Cheol Suh; In-Sun Yoon (Plant Molecular Biology, 2006)

Production of Indole-3-Acetic Acid in the Plant-Beneficial Strain Pseudomonas chlororaphis O6 Is Negatively Regulated by the Global Sensor Kinase GacS - Beom Ryong Kang; Kwang Yeol Yang; Baik Ho Cho; Tae Ho Han; In Seon Kim; Myung Chul Lee; Anne J. Anderson; Young Cheol Kim (Current Microbiology, 2006)

Lidocaine hydrochloride-sodium bicarbonate as an anesthetic for soft-shelled turtle Pelodiscus sinensis - In-Seok PARK; Sung Hwoan CHO; Jun Wook HUR; Gyeng-Cheol CHOI; Sung-Yong OH; Dong Soo KIM; Jae-Seong LEE (Fisheries Science, 2006)

Isolation and characterization ofPanax ginseng 14-3-3 gene family - Hwa -Jee Chung; Joo Young Park; In Sook Cho; Cheol Goo Hur; Dong -Woog Choi; Jang Ryol Liu (Journal of Plant Biology, 2004)

Changes in gene expression during hairy root formation byAgrobacterium rhizogenes infection in ginseng - Hwa -Jee Chung; In Sook Cho; Jee -Hyub Kim; Dong Su In; Cheol Goo Hur; Ji Sook Song; Sung Sick Woo; Dong -Woog Choi; Jang Ryol Liu (Journal of Plant Biology, 2003)